2019
DOI: 10.26633/rpsp.2019.71
|View full text |Cite
|
Sign up to set email alerts
|

Atención inicial de migrantes en Chile: iniciativa en atención primaria de salud a un año de su implementación

Abstract: Objetivo. Describir las características sociodemográficas, necesidades de salud, derivaciones efectivas realizadas y evaluación inmediata de la población migrante internacional que participó en el Programa de Atención Inicial al Migrante durante el primer año de ejecución (entre mayo y diciembre del año 2016), implementado en el Centro de Salud Familiar Ignacio Domeyko, Santiago de Chile. Métodos. Estudio descriptivo. Se diseñó e implementó una intervención para dar bienvenida a migrantes internacionales, que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
4
0
13
Order By: Relevance
“…Regarding the social determinants of health identified in the previous section and their relation to the Chilean segmented healthcare system, female immigrants are more likely to be beneficiaries of the public system than men, 68,4% and 61,7% respectively [ 21 ]. Although there has been a decrease in the rate of immigrants reporting having no health insurance, immigrants with disabilities are more likely to report no healthcare or insurance than Chileans, indicating horizontal inequity (less attention and resources despite similar needs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the social determinants of health identified in the previous section and their relation to the Chilean segmented healthcare system, female immigrants are more likely to be beneficiaries of the public system than men, 68,4% and 61,7% respectively [ 21 ]. Although there has been a decrease in the rate of immigrants reporting having no health insurance, immigrants with disabilities are more likely to report no healthcare or insurance than Chileans, indicating horizontal inequity (less attention and resources despite similar needs).…”
Section: Resultsmentioning
confidence: 99%
“…A study carried out in 2016 focused on a programme aimed at promoting access of the migrant population to primary healthcare ( Programa de Atención Inicial a Migrantes ), found that very few of the programme participants were referred to mental healthcare units despite the fact that they had been assessed for suicidal behaviour and symptoms of depression. A possible explanation put forward by the authors is that there are different conceptions of mental illness across different cultures, whereby international migrants might not find receiving attention necessary [ 21 ]. Similarly, but with regards to healthcare in general, there are cultural barriers regarding perceptions and beliefs around health as reported by health professionals [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En Chile el Plan Nacional de Salud Bucal 2018-2030 incorpora dentro del tercer eje estratégico (investigación-monitoreo-evaluación) la evaluación y monitoreo de los programas de salud pública, evaluando la cobertura de los programas de salud bucal considerando los DSS e incluyendo las variables de situación de discapacidad, etnia, migración y ruralidad. Todo esto en concordancia con la Política de Salud del Migrante Internacional y el derecho a salud del migrante, iniciativa que promueve una mirada inclusiva de la migración desde el enfoque de los derechos humanos, con enfoque de salud intercultural que permita dar la bienvenida al sistema de salud a la población migrante internacional 20 .…”
Section: Presentación Clíncaunclassified
“…En Chile, en el año 2017 se registró un aumento del 33% de la población migrante sobre del promedio de la OCDE (Chepo et al, 2019). Debido a esto, el Estado actualizó su política migratoria y las leyes, además de los procedimientos para regular el ingreso de los extranjeros (Grande y García, 2019).…”
Section: Introductionunclassified